Pendekatan Heutatogi Berbasis Learning Management System Dalam Pembelajaran Sejarah Sebagai Upaya Meningkatkan Kesadaran Sejarah - Tika Salimah Tumanggor (Widya Winayata : Jurnal Pendidikan Sejarah, 2022)
Learning is often considered a boring, uninteresting, and difficult to reach lesson. This is because the concept of learning is focused on a series of years or events that must be recalled during the exam. Seeing these conditions is certainly very fun if students are only able to master the material without taking the wisdom or meaning of the learning. Management of learning subjects at the high school level is experiencing difficulties due to the Covid-19 pandemic which limits human movement. Changes in learning conditions from face to face to online have an impact on the delay in the history learning process at the high school level. The teacher's role is minimized due to not getting the opportunity to have direct or face-to-face dialogue. This study uses a qualitative method with a descriptive approach to describe an object or objects under study. The Heutatogy approach based on the Learning Management System in history learning has become the focus of research in the midst of changes in the learning system during the Covid-19 Pandemic which requires educational facilities to implement the Distance Learning (PJJ) system and also affects efforts to increase the meaning of history.